PEMIKIRAN IBNU SAHNUN TENTANG BELAJAR MENGAJAR AL-QUR’AN - Ahmad Ubaedi Fathuddin (IAIN Pekalongan, 2010)
Ibn Sahnun was the first Islamic leaders in which his thoughts was concentrated in the areas of education, especially teaching the Qur’an to early childhood. The highlighting of Sahnun’s was based on the notion that the Qur’an is the source of knowledge, and learning at an early age would be so attached and rooted in the child. Through Adab al-Mu’allimin, it is known that the thought of Ibn Sahnun seemed complete and programmed well, especially for the classical era in which only a few leaders who pursued the field of education. And of those concepts can be found some things that are still relevant for today, especially about the emphasis on methods of reading, memorizing and understanding in studying the Qur’an, as apparent in the method of iqra ¸ qira’ati, and amtsilati, and the permissibility of a Qur’an teacher to receive, take or set wages from his students